Korea - Caribbean youth exchange program, July 27 (Sun.) - August 4 (Mon.), 2014 (The Foundation KP, 2014)
Presents the programme of activities for the international cultural youth exchange between Korean and the Caribbean.
Keywords: CULTURAL COOPERATION